Discovery of Phosphorylated Peripherin as a Major Humoral Autoantigen in Type 1 Diabetes Mellitus. Issue 5 (19th May 2016) - Doran, Todd M.; Morimoto, Jumpei; Simanski, Scott; Koesema, Eric J.; Clark, Lorraine F.; Pels, Kevin; Stoops, Sydney L.; Pugliese, Alberto; Skyler, Jay S.; Kodadek, Thomas
Summary: A major goal in understanding autoimmune diseases is to define the antigens that elicit a self-destructive immune response, but this is a difficult endeavor. In an effort to discover autoantigens associated with type 1 diabetes (T1D), we used epitope surrogate technology that screens combinatorial libraries of synthetic molecules for compounds that could recognize disease-linked autoantibodies and enrich them from serum. Autoantibodies from one patient revealed a highly phosphorylated form of peripherin, a neuroendocrine filament protein, as a candidate T1D antigen. Peripherin antibodies were detected in 72% of donor patient sera. Further analysis revealed that the T1D-associated antibodies only recognized a dimeric conformation of peripherin. These data explain why peripherin was dismissed as an important T1D antigen previously. The discovery of this novel autoantigen would not have been possible using standard methods, such as hybridizing serum antibodies to recombinant protein arrays, highlighting the power of epitope surrogate technology for probing the mechanism of autoimmune diseases. Graphical Abstract: Highlights: Chemical "epitope surrogates" are selective affinity probes for T1D-related IgG Affinity-purified antibodies bind to the neuroendocrine protein, peripherin Serum antibodies from T1D patients recognize dimeric peripherin Phosphorylation of peripherin is critical for T1D antibody recognition Abstract : Characterizing the autoantigens that trigger adaptive immune responses is challenging, especially when epitopes are non-linear or post-translationally modified. Using "epitope surrogate" small molecules to purify disease-linked antibodies from serum, Doran et al. demonstrate that phosphorylated peripherin is a major autoantigen in patients with type 1 diabetes.